The complete chloroplast genome of Nymphaea thermarum (Nymphaeaceae) from Rwanda, Africa - Maolin Lei; Yiheng Hu (Mitochondrial DNA. Part B. Resources, 2022)
Nymphaea thermarum is classified in the Nymphaeaceae, and is the smallest water lily in the world. It has been extinct its native environment and needs urgent protection. Here, we report and characterize the complete chloroplast genome of N. thermarum. The total length of the chloroplast genome is 159,849 bp and the GC content is 39.2% (A: 30.1%, C: 20.0%, G: 19.2%, T: 30.8%). The chloroplast genome consists of 8 rRNA, 37 tRNA, and 85 protein-coding genes. Phylogenetic analysis of N. thermarum fully resolved this taxon in a clade with Nymphaea capensis. The chloroplast genome of N. thermarum provides scientific guidance for its conservation genetics and also contributes genome resources for the phylogenetic relationship of Nymphaea.